Literature Review: Hubungan Pengetahuan dan Perilaku Masyarakat tentang PSN dengan Keberadaan Jentik Aedes aegypti - Evorius Oriwarda; Lisda Hayatie; Djalalluddin Djalalluddin (Homeostasis, 2021)
Abstract: Dengue fever is a disease caused by dengue virus infection belonging to the family Flaviviridae and the genus Flavivirus transmitted through the bite of the Aedes aegypti mosquito. DEND is found in tropical and sub-tropical lands including Southeast Asia, the Americas, Central America, and the Caribbean Islands. Vector control of DBD can be done in various ways, among others, eradication of mosquito nests (PSN) includes 4M plus: washing, bury or recycle, close, monitor larvae periodically. Some factors that influence the eradication of mosquito nests and the presence of mosquito larvae include knowledge and behavior. The purpose of writing this literature review is to provide an overview of the relationship of knowledge and behavior of the community about PSN with the existence of larvae Aedes aegypti. Writing is done by searching for Indonesian articles published in 2010-2020 using a database of medical journals, with searches using Google Scholar and Garuda. The method used is a narrative review. The conclusion of the literature review obtained 55.5% of articles stating that there is a relationship of knowledge about PSN with the existence of larvae Aedes aegypti and 82.3% of articles stated that there is a relationship between PSN behavior and the presence of Aedes aegypti flicks. The conclusion of the literature review is the relationship of knowledge and behavior about PSN with the existence of larvae Aedes aegypti. Keywords: knowledge, behavior, Aedes aegypti larvae, mosquito eradication. Abstrak: Demam berdarah dengue (DBD) adalah penyakit yang disebabkan oleh infeksi virus dengue yang termasuk dalam famili Flaviridae dan genus Flavivirus yang ditularkan melalui gigitan nyamuk Aedes aegypti. DBD di temukan di daratan tropis dan sub tropis diantaranya Asia Tenggara, Amerika, Amerika Tengah, dan Kepulauan Karibia. Pengendalian vektor DBD dapat dilakukan dengan berbagai cara antara lain pemberantasan sarang nyamuk (PSN) meliputi 4M plus yaitu: menguras, mengubur atau mendaur ulang, menutup dan memantau jentik secara berkala. Faktor yang mempengaruhi keberadaan jentik nyamuk antara lain adalah pengetahuan dan perilaku. Tujuan penulisan literature review ini untuk memberikan gambaran tentang hubungan pengetahuan dan perilaku masyarakat tentang PSN dengan keberadaan jentik Aedes aegypti. Penulisan dilakukan dengan menelusuri artikel berbahasa Indonesia yang diterbitkan tahun 2010-2020 menggunakan database jurnal kedokteran, dengan pencarian menggunakan Google Scholar dan Garuda. Metode yang digunakan adalah narrative review. Hasil penelusuran 18 artikel didapatkan 55,5% artikel yang menyatakan terdapat hubungan pengetahuan tentang PSN dengan keberadaan jentik Aedes aegypti dan 82,3% artikel menyatakan terdapat hubungan perilaku PSN dengan keberadaan jentik Aedes aegypti. Kesimpulan dari literature review terdapat hubungan pengetahuan dan perilaku tentang PSN dengan keberadaan jentik Aedes aegypti. Kata-kata kunci: pengetahuan, perilaku, jentik Aedes aegypti, PSN